Effect of complex decongestive therapy on frailty and quality of life in women with breast cancer-related lymphedema: the before-and-after treatment study - Kavak, Songül Keskin; Ünver, Gamze (Frontiers in Oncology, 2024)
Objective: To investigate the impact of Complex Decongestive Therapy (CDT) on the severity of frailty and quality of life in individuals suffering from postmastectomy lymphedema syndrome.Participants who met the inclusion criteria were informed about CDT and informed consent was obtained. Edmonton Frailty Scale (EFS), extremity volüme (EV), lymphedema stage(LS), EQ-5D General Quality of Life Scale (EQ-5D-5L), and Quick Disabilities of Arm, Shoulder, and Hand (DASH) scores were evaluated by the same physician before and after treatment. A total of 15 sessions of CDT were performed for 3 weeks, five days a week. During the treatment period, hospitalized patients received guidance from a nurse on protecting the affected arm in their daily routine.Results: Eighty patients with breast cancer-related lymphedema who met the inclusion criteria were included in the study. Following a period of 3 weeks of practice and training, the specialist physician conducted the final evaluation and assessments. All patients showed a statistically significant reduction in EV, and regression in LS, EFS, and Quick DASH score (p<0.001).Statistically significant improvement was also observed in quality of life and general health status. (p<0.001).The application of 15 sessions of CDT and educational interventions to women with postmastectomy lymphedema syndrome due to breast cancer yielded positive outcomes. This approach led to an enhancement in patients' functional capacity, improving their quality of life and a subsequent reduction in the severity of frailty.